Предмет: Алгебра,
автор: Валкок
sin(п - 2d) + 2cos(3п : 2 + d) sin(3п : 2 - d)=
Ответы
Автор ответа:
0
Решение
Sin(п - 2d) + 2cos(3п : 2 + d) sin(3п : 2 - d) = sin2d + 2sind * (- cosd) =
= sin2d - 2sindcosd = sin2d - sin2d = 0
Sin(п - 2d) + 2cos(3п : 2 + d) sin(3п : 2 - d) = sin2d + 2sind * (- cosd) =
= sin2d - 2sindcosd = sin2d - sin2d = 0
Похожие вопросы
Предмет: Русский язык,
автор: vladislav20070910
Предмет: Алгебра,
автор: kimmia468
Предмет: Информатика,
автор: dbyrcv
Предмет: География,
автор: ъхэ
Предмет: Математика,
автор: Yagamraito666